Comprehensive screening for PD-L1 expression in thyroid cancer. Issue 2 (February 2017) - Ahn, Soomin; Kim, Tae Hyuk; Kim, Sun Wook; Ki, Chang Seok; Jang, Hye Won; Kim, Jee Soo; Kim, Jung Han; Choe, Jun-Ho; Shin, Jung Hee; Hahn, Soo Yeon; Oh, Young Lyun; Chung, Jae Hoon
Abstract : PD-L1 expression is being considered a potential biomarker for response of anti-PD-1 or anti-PD-L1 agents in various tumors. The reported frequency of PD-L1 positivity varies in thyroid carcinomas, and multiple factors may contribute to the variability in PD-L1 positivity. We evaluated the PD-L1 expression in various thyroid cancers on a large scale. A total of 407 primary thyroid cancers with a median 13.7-year of follow-up were included. We evaluated the frequency of PD-L1 expression using a rabbit monoclonal antibody (clone SP142). In addition, we analyzed the relationships between PD-L1 expression and clinicopathologic factors, including TERT promoter, BRAF status and disease progression. Tumoral PD-L1 was expressed in 6.1% of papillary thyroid carcinomas, 7.6% of follicular thyroid carcinomas and 22.2% of anaplastic thyroid carcinomas. The distribution of PD-L1 positivity was different according to cancer histology types ( P  < 0.001). All PD-L1-positive cases of follicular thyroid carcinoma and anaplastic thyroid carcinoma showed strong intensity. The proportions of positivity in PD-L1 positive anaplastic thyroid carcinomas were more than 80%. PD-L1 in immune cells was positive in 28.5% of papillary thyroid carcinoma, 9.1% of follicular thyroid carcinomas and 11.1% of anaplastic thyroid carcinomas. There was no significant association between clinicopathologic variables, disease progression, oncogenic mutation and PD-L1 expression. PD-L1 was highly expressed in a subset of patients with advanced thyroid cancer, such as follicular and anaplastic thyroid carcinoma. Identification of PD-L1 expression may have direct therapeutic relevance to patients with refractory thyroid cancer.